Larval exposure to sertraline induces dose- and time-dependent remodeling of neuronal alternative splicing in adult Drosophila melanogaster - Luis Felipe Santos-Cruz; Myriam Campos-Aguilar; Laura Castañeda-Partida; María Eugenia Heres-Pulido; Irma Elena Dueñas-García; Elías Piedra-Ibarra; Rafael Jiménez-Flores; Alberto Ponciano-Gomez (Molecular Biology Reports, 2026)
Background Alternative splicing is a central procedure that increases the variety of the transcriptome and helps regulate several neuronal processes. Various pharmacological factors have the capacity to alter splicing patterns, which could potentially affect cellular function. Sertraline, a selective serotonin reuptake inhibitor widely used in the treatment of neuropsychiatric disorders, also regulates intracellular pathways linked with calcium signaling and other cellular processes. However, information about its potential impact on the post-transcriptional regulation of the transcriptome is still insufficient. Methods and Results In this study, we analyzed whether exposure to sertraline changes alternative splicing patterns in the neural transcriptome of Drosophila melanogaster. Third-instar larvae were exposed to two concentrations of the drug during different periods of time, and the RNA obtained from adult heads was analyzed by RNA sequencing (RNA-seq). The evaluation of differential splicing revealed modifications that depend on the experimental condition in exon usage, including exon skipping, intron retention, and alternative splice-site selection. The affected genes showed functional enrichment in processes related to ion transport, synaptic organization, and neuronal signaling. The in silico reconstruction and translation of representative isoforms indicated possible modifications in protein architecture, including predicted loss of domains or truncations. Conclusions Taken together, these results indicate that sertraline can remodel alternative splicing in the neuronal transcriptome in a manner dependent on dose and exposure time. These findings suggest a possible additional mechanism through which larval sertraline exposure could influence neuronal function via persistent remodeling of RNA processing in adult neural tissue, as inferred from RNA-seq-based transcriptomic analyses.

A methodological approach for evaluating hydrocarbon generation potential using 1D petroleum system modelling: A case study from the Sabinas Basin, Northeastern Mexico - Juan Josué Enciso-Cárdenas; Genaro de la Rosa-Rodríguez; Diana Margarita Garza-Cavazos; Diego de Jesús Martínez-Hernández; Aurea Yahaira González-Betancourt; Fernando Núñez-Useche; Luis Fernando Camacho-Ortegón; Eduardo González-Partida; Jordan Ortiz-Treviño; Yuriko Yarel Bueno-Yamamoto (Ore and Energy Resource Geology, 2026)

Modelling Nature-Based Solutions in HEC-RAS - Ramtin Sabeti; Thomas Rodding Kjeldsen; Matt Chambers; Hamed Moftakhari; Luis Partida; Ioanna Stamataki; Solomon Simmonds; Rebecca Lee; Barry Hankin; Melissa Hoskings; Katherine Dixon; James Molloy; et al. (Water Resources Management, 2026)
Nature-based solutions (NBS) are becoming increasingly popular for mitigating flood risk while providing multiple benefits such as enhanced biodiversity, and improved water quality. Hydraulic modelling is an essential tool for evaluating and optimising the flood risk regulating service of NBS. Yet, there is no standardised approach to represent NBS interventions in hydraulic models, leading to inconsistent implementations. This study reports a systematic review of 1,080 publications from Scopus and Web of Science. A final selection of 30 key-studies is identified utilising HEC-RAS to model NBS interventions. By collating and synthesising the various approaches documented in these studies, a consolidated resource for researchers and practitioners is provided. This synthesis offers practical recommendations for the application of different NBS interventions in hydraulic modelling and outlines the corresponding parameter ranges to consider. A critical assessment is undertaken on how these interventions map to specific parameters in the governing hydraulic equations, elucidating the physical mechanisms of flow attenuation and water storage that are broadly applicable to all hydraulic models. To demonstrate the real-world utility of these recommendations, a case study of the River Chew catchment (England) is presented, detailing pre- and post-intervention configurations wherein multiple candidate areas are converted to wetland and woodland using a HEC-RAS 2D model; this section is available in the Supplementary Material. Graphical Abstract

Coal facies of the Olmos Formation in the Sabinas Basin, Northeastern Mexico - Genaro de la Rosa-Rodríguez; Juan Josué Enciso-Cárdenas; Cristina Fernanda Alves Rodrigues; Manuel João Lemos de Sousa; Luis Fernando Camacho Ortegón; Eduardo González-Partida; Yuriko Yarel Bueno Yamamoto (Journal of South American Earth Sciences, 2025)

Phenome-wide screening of GWAS data reveals the complex causal architecture of obesity - Luis M. García-Marín; Adrián I. Campos; Pik-Fang Kho; Nicholas G. Martin; Gabriel Cuéllar-Partida; Miguel E. Rentería (Human Genetics, 2021)

The environmental legacy of the Ixtoc-I oil spill in Campeche Sound, southwestern Gulf of Mexico - Luis A. Soto; Alfonso V. Botello; Sergio Licea-Durán; Marcial L. Lizárraga-Partida; Alejandro Yáñez-Arancibia (Frontiers in Marine Science, 2014)

De novo inv(17)(p11.2q21.3) in an intellectually disabled girl: appraisal of 21 inv(17) constitutional instances - MIRIAM PARTIDA-PÉREZ; MARÍA G. DOMÍNGUEZ; VIVIAN ALEJANDRA NEIRA; LUIS E. FIGUERA; HORACIO RIVERA (Journal of Genetics, 2012)

Toxic and trace metal concentrations in liver and kidney of dogs - Marta López-Alonso; Marta Miranda; Paulino García-Partida; Adriana Mendez; Cristina Castillo; José Luis Benedito (Biological Trace Element Research, 2007)

Toxic and trace metal concentrations in liver and kidney of dogs - Marta López-Alonso; Marta Miranda; Paulino García-Partida; Adriana Mendez; Cristina Castillo; José Luis Benedito (Biological Trace Element Research, 2007)